Decision Support System for Accepting Pre-Employment Cards during the Covid-19 Pandemic Using the Method Multi Objective Optimization on The Basic of Ratio Analysis (MOORA) - Chandra Frenki Sianturi; Lince Tomoria Sianturi; Uswatun Hasanah; Khairunnisa Khairunnisa; Mesran Mesran (STMIK Budi Darma, 2021)
During the Covid-19 pandemic there were many impacts on the community such as social, educational and financial problems, therefore the government as the highest authority in society made a policy for the Pre-Work Card program as a solution to one of the problems, especially in the economic sector that was felt by the community, such as overcoming the problem of unemployment, layoffs, and poverty. With the help of the Decision Support System, it is hoped that they will be able to make the best decisions for prospective Pre-Employment Card recipients. This study aims to determine the best alternative that fits the criteria according to the requirements of the Pre-Work Card by using the MOORA (Multi Objective Optimization On The Basic Of Ratio Analysis) method